Modified partial circumcision for phimosis: techniques and surgical outcomes. Issue 3 (July 2018) - Arena, Salvatore; Impellizzeri, Pietro; Parisi, Saveri; Perrone, Patrizia; Russo, Tiziana; Romeo, Carmelo
Abstract : Objectives: In the last years, many surgical techniques of preputioplasty have aimed to preserve the foreskin in case of phimosis. These techniques are not reliable for patients affected by phimosis linked to balanitis xerotica obliterans (BXO) and scarred foreskin. We tried an original technique of resection of the pathological foreskin, removing the mucosal internal layer followed by reconstruction of the foreskin. The aim was to evaluate the outcome of paediatric patients who underwent modified partial circumcision for pathological phimosis. Patients and methods: In all, 360 patients with phimosis underwent modified partial circumcision at our institution. The mean age of the boys was 8.9 years, range 5–15 years. In 145 (40.3%) cases, indication for surgery was clinical suspicion of BXO, in 215 (59.7%) cases it was chronic inflammation of the foreskin. Results: In all cases, the postoperative period was uneventful. Cosmesis was considered by parents as excellent in 95.2% of patients. In these patients, the glans was almost completely covered by soft foreskin. Histopathological examination of the removed foreskin documented BXO in 162 (45%). Twelve (3.3%) patients complained of recurrences and five (1.4%) patients of smegmatic cysts. Conclusion: The described surgical technique of modified partial circumcision for the correction of pathological phimosis appears cosmetically well accepted, safe, and simple with low rate of late postoperative complications.